Biological effects in normal cells exposed to FLASH dose rate protons. (October 2019) - Buonanno, Manuela; Grilj, Veljko; Brenner, David J.
Highlights: This is the first study on long term effects of proton irradiations at FLASH dose rate in vitro . Proton dose rate has little impact on acute effects in normal cells. Cell survival and γH2AX foci formation depend weakly on proton dose rate. Protons delivered at FLASH dose rates mitigate long-term adverse effects in normal cells. Increase in proton dose rate reduces the number of senescent cells and cellular levels of TGFβ1. Abstract: Background: Radiotherapy outcomes are limited by toxicity in the healthy tissues surrounding the irradiated tumor. Recent pre-clinical studies have shown that irradiations with electrons or photons delivered at so called FLASH dose rates (i.e. >40 Gy/s) dramatically reduce adverse side effects in the normal tissues while being equally efficient for tumor control as irradiations at conventional dose rates (3–5 cGy/s). In the case of protons however, FLASH effects have not been investigated partially because of the limited availability of facilities that can achieve such high dose rates. Methods: Using a novel irradiation platform, we measured acute and long-term biological effects in normal human lung fibroblasts (IMR90) exposed to therapeutically relevant doses of 4.5 MeV protons (LET = 10 keV/µm) delivered at dose rates spanning four orders of magnitude. Endpoints included clonogenic cell survival, γH2AX foci formation, induction of premature senescence (β-gal), and the expression of the pro-inflammatory marker TGFβ. Results: Proton dose rate had no influence on the cell survival, but for the highest dose rate used (i.e. 1000 Gy/s) foci formation saturated beyond 10 Gy. In the progeny of irradiated cells, an increase in dose (20 Gy vs. 10 Gy) and dose rate (1000 Gy/s vs. 0.05 Gy/s) positively affected the number of senescence cells and the expression of TGFβ1. Conclusions: In normal lung fibroblasts proton dose rate had little impact on acute effects, but significantly influenced the expression of long-term biological responses in vitro . Compared to conventional dose rates, protons delivered at FLASH dose rates mitigated such delayed detrimental effects.